The Community Relations Strategy Through the 9th NextDev Program as the Implementation of Corporate Social Responsibility by PT Telekomunikasi Selular (Telkomsel) - Dhea Andita Sari Saroso; Mochammad Kresna Noer (ULTIMA Comm, 2024)
The growth of digital startups in Indonesia faces major challenges, including limited access to funding, low digital literacy, and uneven infrastructure, which hinder business sustainability. PT Telekomunikasi Selular (Telkomsel), through its CSR program "9th NextDev" themed Growing to Inspire, aims to address these issues by strengthening the digital startup ecosystem using a community relations approach. This program serves as a strategic initiative to drive digital innovation while supporting social sustainability within Indonesian communities. This study explores Telkomsel's community relations strategy in building sustainable relationships with digital startup communities. The focus is on how the 9th NextDev program supports training, business development, and the empowerment of digital communities as part of the company's corporate social responsibility (CSR). Using a qualitative case study approach, this research applies Edmund M. Burke's theory, which includes three main pillars: Building Sustainable Relationships of Trust, Managing Community Issues and Concerns, and Using Community Support Programs to Build Trust. The findings indicate that the program successfully establishes sustainable relationships through transparent information sharing, two-way communication, and active community engagement. To address community issues, the program identifies the specific needs of startups, resolves conflicts, and responds promptly to challenges such as limited digital literacy and technology adoption in regions with inadequate infrastructure. Through mentoring, technical training, and access to business networks, the program strengthens the foundation of startups and fosters inclusivity. Despite persistent infrastructure challenges, socially relevant technology-based solutions have enabled 9th NextDev to enhance startup sustainability while boosting Telkomsel's reputation as a leader in sustainable digital innovation in Indonesia.